Effective Utilization of Photovoltaic Energy Using Multiphase Boost Converter in Comparison with Single Phase Boost Converter - Jan Perdulak; Dobroslav Kovac; Irena Kovacova; Matus Ocilka; Andrii Gladyr; Dmytro Mamchur; Iurii Zachepa; Tibor Vince; Jan Molnar (Communications - Scientific letters of the University of Zilina, 2013)
The paper presents a novel concept of multiphase boost converter (MPBC) with high efficiency of energy conversion. The new topology of MPBC is compared with conventional single-phase boost converter (SPBC). It is shown that almost whole input energy from photovoltaic module entering to the proposed MPBC is utilized more effectively in comparison with conventional SPBC. This effective energy utilization is ensured by suitable algorithm of switches control. Modeling, simulation and experimental results are given. Subsequently the laboratory models of SPBC and MPBC were built and experimental results were obtained to confirm the simulation results. Also the control module of MPBC was designed, simulated and built to ensure the correct operation of proposed converter.